2012 Asia-Pacific Symposium on Electromagnetic Compatibility 2012
DOI: 10.1109/apemc.2012.6237825
|View full text |Cite
|
Sign up to set email alerts
|

Radiated EMI coupling analysis between high-speed modules and receiving antennas of mobile devices

Abstract: This study mainly investigates the impact of high speed digital modules' radiated EMI noise on receiving performance of wireless mobile device via built-in antenna coupling. We began with designing dipole and loop antenna to represent the routing and trace pattern for common-and differential-mode current flowing inside digital modules installed in mobile devices(such as Tablet, Notebook computers, and smart phones), and then observed the coupling effect of their EMI noise on receiving antenna ports. Utilizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…The noise measurement results show that the 125 MHz harmonic is the primary source of noise on the digital circuit board. There are actual case studies of this phenomenon in [3,15]. When there is built-in base frequency in the function module of mobile device, such as the harmonic frequencies of USB 48 MHz, LVDS 65 MH, and LAN chip 25 MHz, EMI noise interference with mobile communication bands have been detected, and this result is consistent with the references.…”
Section: Verification Of Digital Circuit Emi Noise Segmentssupporting
confidence: 80%
See 1 more Smart Citation
“…The noise measurement results show that the 125 MHz harmonic is the primary source of noise on the digital circuit board. There are actual case studies of this phenomenon in [3,15]. When there is built-in base frequency in the function module of mobile device, such as the harmonic frequencies of USB 48 MHz, LVDS 65 MH, and LAN chip 25 MHz, EMI noise interference with mobile communication bands have been detected, and this result is consistent with the references.…”
Section: Verification Of Digital Circuit Emi Noise Segmentssupporting
confidence: 80%
“…Electromagnetic compatibility (EMC) studies have revealed that the most effective solution for dealing with EMI is to focus on the source of the noise. Recent studies also showed that IC noise is a leading cause of EMI [1][2][3]. IC noise can be measured and analysed to effectively assess the key issue(s) leading to EMI in electronics products.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the contraint for antenna placement, studies of RFI coupling, which is dependent on the placement of radiated emission sources instead of antennas, have been introduced. The impact of the radiated emission generated from digital interconnects, which include passive routing and trace patterns used as radiated emission sources, on built‐in antennas in wireless mobile devices has been investigated . To expand the radiated emission sources from the passive interconnects to digital ICs, RFI estimation using a real IC has been conducted .…”
Section: Introductionmentioning
confidence: 99%